Kid Learn - Kong, Choon (2023)
The study aims to address the challenge of vocabulary development in children and propose a solution using technology. Vocabulary is essential for effective communication and information acquisition, and its development is crucial, especially in second language learning. One effective way to enhance vocabulary development in children is by incorporating technology into their learning experience. To address this issue, we propose a new mobile application called Kid Learn with AR Visualization. This application is designed for children between the ages of 3 and 12, and it allows them to learn new vocabulary words through play and interactive experiences. The application includes augmented reality (AR) technology, which enhances the real world with digital visual elements, audio, or other sensory stimuli, making the learning experience more fun and interactive. The application will provide an AR-enhanced learning experience where children can choose from a variety of categories, and objects will be displayed on their mobile screens based on their choices. The application also includes quiz questions and puzzle games to reinforce the children's memory. The development process of the application will be guided by the Rapid Application Development (RAD) software development methodology, which is flexible and allows for rapid changes during the development process. The implementation of this application is expected to provide children with a fun and interactive way to learn new vocabulary words, which will in turn enhance their language skills and improve their overall education experience. Furthermore, incorporating technology into education is becoming increasingly important in today's world, and this application is in line with this trend. In conclusion, the Kid Learn with AR Visualization application is an innovative solution to the challenge of vocabulary development in children and represents a new form of learning that incorporates technology in an engaging way. The development of this application will provide children with a fun and interactive way to learn new vocabulary words and will contribute to their overall educational experience.